2013
DOI: 10.1016/j.spinee.2012.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of metalloproteinases and their inhibitors in intervertebral disc aging and degeneration

Abstract: BACKGROUND CONTEXT Destruction of extracellular matrix (ECM) leads to intervertebral disc degeneration (IDD), which underlies many spine-related disorders. Matrix metalloproteinases (MMPs), and disintegrins and metalloproteinases with thrombospondin motifs (ADAMTSs) are believed to be the major proteolytic enzymes responsible for ECM degradation in the intervertebral disc (IVD). PURPOSE To summarize the current literature on gene expression and regulation of MMPs, ADAMTSs, and tissue inhibitors of metallopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
311
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(322 citation statements)
references
References 99 publications
(147 reference statements)
4
311
0
7
Order By: Relevance
“…− on the level of altering gene expression in patients with a genetic predispositions [26]; − on the level of transcription by cytokines (IL-1, TNF), hormones (parathormone, PTH) and bacteria products (LPS); − on the level of enzyme sequestration to intracellular bubbles; − on the level proenzyme activation (metal ions, oxidative stress, detergents, other proteolytic enzymem, plasmin); − on the level of substrate specificity; − through the pH of the environment; − through tissue inhibitors of metalloproteinases (TIMPs) and serine protease inhibitors (serpins) [27].…”
Section: The Regulation Of Mmpsmentioning
confidence: 99%
“…− on the level of altering gene expression in patients with a genetic predispositions [26]; − on the level of transcription by cytokines (IL-1, TNF), hormones (parathormone, PTH) and bacteria products (LPS); − on the level of enzyme sequestration to intracellular bubbles; − on the level proenzyme activation (metal ions, oxidative stress, detergents, other proteolytic enzymem, plasmin); − on the level of substrate specificity; − through the pH of the environment; − through tissue inhibitors of metalloproteinases (TIMPs) and serine protease inhibitors (serpins) [27].…”
Section: The Regulation Of Mmpsmentioning
confidence: 99%
“…Tissue engineering approaches often combine growth factors and cells to attempt to repair the nucleus pulposus; however, in the harsh catabolic environment of the degenerating disc, growth factors and cells cannot survive [15][16][17][18][19][20]. The addition of a biomaterial carrier has the potential to increase cell viability and enable long-term growth factor delivery.…”
Section: Introductionmentioning
confidence: 99%
“…However, the anulus fibrosus becomes weaker with increasing age (3), resulting in intervertebral disc degeneration (IDD). Beyond age 40, >60% of individuals show symptoms of IDD; furthermore, IDD is the most common cause of disability among workers aged 18-64 years (4). IDD is characterized by decreases in intervertebral disc function and height due to cell loss through apoptosis, increased breakdown of matrix or altered matrix synthesis, with the underlying pathological processes being complex (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Vo et al (4) reported that IDD was a consequence of increased catabolism of the extracellular matrix (ECM), since the proteolytic degradation of ECM macromolecules led to marked structural changes of the intervertebral disc. These catabolic processes are mediated by a number of cytokines in the nucleus pulposus, among which interleukin (IL)-1β and tumor necrosis factor (TNF)-α have been suggested to have crucial roles in the development of IDD.…”
Section: Introductionmentioning
confidence: 99%